Color discrimination properties arising from optimal decoding in the early stages of visual systems - Risau Gusman, Sebastian Luis (Academic Press Ltd - Elsevier Science Ltd, 2021)
Fil: Risau Gusman, Sebastian Luis. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte; Argentina. Comisión Nacional de Energía Atómica. Centro Atómico Bariloche; Argentina